1995
DOI: 10.1007/bf00750523
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance and root behavior in four pigeonpea-based intercropping systems

Abstract: Fert~ilzer Research publishes orlglnal papers and short cornmun~catlons based on research results as well as Ilteratureand book reviews dealmy wlth fertillzers and so11 fertil~ty management Occasionally, specla1 Issues w~ll be ded~cated to the proceedings of symposla and workshops Contr~butlons are accepted In the f~elds of inorganic, organlc and b~ofertlllzers In relation to crop and forest producl~on and qual~ty, so11 productlv~ty as related to so11 fertlllty chem~stry and rn~crob~oloyy, and the env~ronmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
3
8
1
Order By: Relevance
“…N addition (i) did not increase the total pea-barley intercrop yield, (ii) decreased the contribution of pea, and (iii) decreased RYT values which remain nevertheless higher than 1. These results are in agreement with other studies on the effect of N fertilizer in intercrops based on legumes and another species (Jensen, 1996;Katayama et al, 1995;Leitch and Musa, 1998;Waterer et al, 1994). Through the use of a soil N competition index, it was shown that RYT values for grain yield and N accumulation remain constant (close to 1) at very low levels of competition and tend to increase while the intensity of competition for soil N increases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…N addition (i) did not increase the total pea-barley intercrop yield, (ii) decreased the contribution of pea, and (iii) decreased RYT values which remain nevertheless higher than 1. These results are in agreement with other studies on the effect of N fertilizer in intercrops based on legumes and another species (Jensen, 1996;Katayama et al, 1995;Leitch and Musa, 1998;Waterer et al, 1994). Through the use of a soil N competition index, it was shown that RYT values for grain yield and N accumulation remain constant (close to 1) at very low levels of competition and tend to increase while the intensity of competition for soil N increases.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous article on root methods, based on the same experiments, we showed that barley has a faster root depth penetration and a higher root biomass compared to pea in intercrops (CorreHellou and Crozat, 2005). Other authors have also demonstrated the advantage of cereals relatively to legumes in terms of root development in intercrops (Hauggaard-Nielsen et al, 2001;Izaurralde et al, 1992;Katayama et al, 1995). Moreover the crop growth of barley takes place earlier than that of pea (Andersen et al, 2005;Bellostas et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Izaurralde et al (1992) observed that root length tended to be higher under pea-barley mixtures than in sole crops. Similar results were quoted in pigeonpea-sorghum mixtures (Katayama et al, 1995). Nevertheless, in these studies, root length was not distinguished according to species.…”
Section: Rooting Patterns In Mixturessupporting
confidence: 83%
“…Van Kassel and Roskoski (1998) reported stiff competition in a cowpea-maize intercrop where the intercropped maize took twice as much N as the cowpea as compared to similar amounts that were taken up in sole crops. However, Katayama et al (1995) observed no significant differences in %N dfa by cowpea in sole cropping and in an intercrop with pigeon pea which was attributed to the indeterminate, spreading and climbing nature of the cowpea variety used in that experiment which gave it an advantage in exploiting resources. The present study has shown that the overall contribution of N per unit area by a cropping system with consideration of both component crops in the pigeon pea-cowpea intercrop (summing up their biologically fixed N) depended on both the system and to some extent the site effects.…”
Section: Discussionmentioning
confidence: 62%
“…Pigeon pea that was intercropped with maize or cowpea faced competition for growth resources including nutrients. Ghosh et al (2006) reported reduction in relative nitrogen yields in pigeon pea when intercropped with soybean, which was attributed to competition for N, whereas Katayama et al (1995) in a similar study in a shallow Alfisol in India reported reduction in %N dfa when pigeon pea was intercropped with various crops including cowpea. Pigeon pea reduction in growth and N 2 fixation as influenced by intercropping with various crops such as maize, soybean, groundnuts or sorghum has been reported in a number of similar studies (Egbe, 2007;Mhango, 2011;Njira et al, 2012: Egbe et al, 2015.…”
Section: Discussionmentioning
confidence: 96%